Factors Affecting Stock Returns in Banking Companies Listed on the Indonesia Stock Exchange: Faktor - Faktor yang Mempengaruhi Return Saham pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Alfi Atus Zumro; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the factors that can affect stock returns in banking companies listed on the Indonesia Stock Exchange (IDX). The period of this reseearch is 2017 – 2020. The population of this study includes all banking companies listed on the IndonesiaStock Exchange (IDX) during the period 2017 – 2020. The sampling technique used is purposive sampling. The results of this study indicate that partially the current ratio (CR) and price to book value (PBV) variable have a significant positive effect on stock returns. Debt to equity ratio (DER) has a significant negative effect on stock returns. Meanwhilw, firm size anf return on assets (ROA)have no significant effection on sktock return. Highlights: Significance of Variables: The study examines the impact of key financial variables such as current ratio, price to book value, and debt to equity ratio on stock returns in Indonesian banking companies. Positive Effects: The current ratio and price to book value are found to have a significant positive influence on stock returns, suggesting their importance as indicators of financial performance and market valuation. Negative Effect of Debt: The study highlights the negative effect of the debt to equity ratio on stock returns, emphasizing the potential risks associated with higher levels of debt in banking companies. Keywords: Stock returns, Banking companies, Indonesia Stock Exchange (IDX), Factors, Purposive sampling.